2002
DOI: 10.1111/j.1349-7006.2002.tb01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of a New Lung Cancer Cell Line (MI‐4) Producing High Levels of Granulocyte Colony Stimulating Factor

Abstract: Some cancer patients manifest leukocytosis without overt inflammation. The production of granulocyte colony-stimulating factor (G-CSF) by the tumor itself is thought to be responsible for this paraneoplastc syndrome.1-3) At least 80 cases of G-CSF-producing tumors have been reported up to the present. Although many types of G-CSF-producing tumors such as carcinoma of the thyroid, 4, 5) kidney, 6) oral cavity, 7) bladder, 8) gallbladder, 9) stomach, 10) hepatoma 11) and melanoma 12) have been reported, carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Despite the fact that we had not investigated the presence in the serum and tumor of any of the cytokines, G‐CSF, GM‐CSF, IL‐6, IL‐1, and TNF cytokines have consistently been reported to be raised in dozens of reports dealing with paraneoplastic leukocytosis, and it has been firmly established that multiple hematopoietic cytokines particularly G‐CSF and GM‐CSF induce autocrine growth promotion in a number of cancer types and tumor models (19,29–35) . Further, TNF‐alpha and IL‐1beta enhance the expression of G‐CSF and GM‐CSF (36) . IL‐6 in particular has also been involved in paraneoplastic leukocytosis in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that we had not investigated the presence in the serum and tumor of any of the cytokines, G‐CSF, GM‐CSF, IL‐6, IL‐1, and TNF cytokines have consistently been reported to be raised in dozens of reports dealing with paraneoplastic leukocytosis, and it has been firmly established that multiple hematopoietic cytokines particularly G‐CSF and GM‐CSF induce autocrine growth promotion in a number of cancer types and tumor models (19,29–35) . Further, TNF‐alpha and IL‐1beta enhance the expression of G‐CSF and GM‐CSF (36) . IL‐6 in particular has also been involved in paraneoplastic leukocytosis in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the presence of an autocrine growth loop for G-CSF 31,32) and GM-CSF 13) in non-hematopoietic tumor cells. However, our cell lines did not have an autocrine growth loop for G-CSF, 27) and they were not investigated for GM-CSF. To our knowledge, there have been no reports about autocrine growth control by G-CSF in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] We showed that the inflammatory cytokines, TNF-α and IL-1β induced COX-2 expression in addition to G-CSF or GM-CSF in OKa-C-1 and MI-4 cells. 27,41) Some studies have reported that NF-κB activa- tion is required to upregulate G-CSF, GM-CSF, or COX-2 expression, [42][43][44][45][46][47][48][49] and that inactivation of the NF-κB also induces rapid pro-apoptotic action. 45) COX-2 activation was also shown to follow the activation of MAPK in another cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In general, surgical tissues have been used to establish human lung cancer cell lines, and various functional lung cancer cell lines have been reported (10)(11)(12). Nonetheless, the incidence of lung cancer remains globally high.…”
Section: Resultsmentioning
confidence: 99%